Teaching, learning, and motivation in a multicultural context - Salili, Farideh; Hoosain, R. (Research in multicultural education and international perspectives., 2003)
The volume 3 of this series is designed to present educators with current research and emerging issues in teaching, learning and motivation in a multicultural context. The book is separated into four sections. In the introduction section we have outlined some of the current issues and recent thoughts about the nature of learning, teaching, and school reforms from a multicultural perspective.